Progestin increases the expression of gonadotropins in pituitaries of male zebrafish. Issue 1 (July 2016) - Wang, Cuili; Liu, Dongteng; Chen, Weiting; Ge, Wei; Hong, Wanshu; Zhu, Yong; Chen, Shi X
Abstract : Our previous study showed that the in vivo positive effects of 17α, 20β-dihydroxy-4-pregnen-3-one (DHP), the major progestin in zebrafish, on early spermatogenesis was much stronger than the ex vivo ones, which may suggest an effect of DHP on the expression of gonadotropins. In our present study, we first observed that fshb and lhb mRNA levels in the pituitary of male adult zebrafish were greatly inhibited by 3 weeks exposure to 10nM estradiol (E2 ). However, an additional 24h 100nM DHP exposure not only reversed the E2 -induced inhibition, but also significantly increased the expression of fshb and lhb mRNA. These stimulatory effects were also observed in male adult fish without E2 pretreatment, and a time course experiment showed that it took 24h for fshb and 12h for lhb to respond significantly. Because these stimulatory activities were partially antagonized by a nuclear progesterone receptor (Pgr) antagonist mifepristone, we generated a Pgr-knockout ( pgr –/– ) model using the TALEN technique. With and without DHP in vivo treatment, fshb and lhb mRNA levels of pgr –/– were significantly lower than those of pgr +/+ . Furthermore, ex vivo treatment of pituitary fragments of pgr –/– with DHP stimulated lhb, but not fshb mRNA expression. Results from double-colored fluorescent in situ hybridization showed that pgr mRNA was expressed only in fshb -expressing cells. Taken together, our results indicated that DHP participated in the regulation of neuroendocrine control of reproduction in male zebrafish, and exerted a Pgr-mediated direct stimulatory effect on fshb mRNA at pituitary level.